Hyperbox Granular Computing Based on Distance Measure - Liu, Hongbing; Guo, Huaping; Wu, Chang-an (International Journal of Control and Automation, 2016)
A bottle up hyperbox granular computing (HBGrC) is developed based on distance measure. Firstly, hyperbox granule is represented by the beginning point and the end point. Secondly, the distance measure between two hyperbox granules is defined by the beginning points and the end points. Thirdly, operations between two hyperbox granules are designed to the transformation between two hyperbox granule spaces with different granularities, HBGrC is developed by the join operator and the user-defined granularity threshold  on the basis of bottle up scheme. Experimental results shown that HBGrC achieved the better testing accuracies over the machine learning benchmark datasets.